Case Report: Complete response to pembrolizumab monotherapy in a geriatric patient with metastatic Merkel cell carcinoma and TNBC - Liu, Jessica; Olino, Kelly; Lustberg, Maryam; Kanowitz, Jane (Frontiers in Oncology, 2025)
We present a case of a 98-year-old patient with metastatic Merkel cell carcinoma (MCC), a rare and aggressive neuroendocrine skin cancer, and locally advanced triple-negative breast cancer (TNBC), who achieved durable remission of both diseases with anti-PD-1 pembrolizumab monotherapy. This case is particularly significant to clinical management of advanced cutaneous malignancy in the elderly, who are historically underrepresented in clinical trials, as it demonstrates the remarkable efficacy of pembrolizumab alone while avoiding toxicities associated with traditional chemotherapy. The regression of the MCC lesion is noteworthy given the typically poor prognosis of metastatic MCC in geriatric patients. This experience contributes to the growing body of evidence supporting immunotherapy as a well-tolerated option for older adult patients with advanced skin and/or breast cancers, particularly when careful toxicity screening is employed for patient selection.